2021
DOI: 10.1002/jeq2.20240
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance gene dissipation in soil microcosms amended with antibiotics and swine manure

Abstract: Antibiotic resistant gene dissipation in soil microcosmsCore ideas (3-5 impact statements, 85 char max for each)The dissipation of manure associated ARGs was not impacted by soil vegetative growth.Five of six quantified ARGs dissipated over time with half-lives ranging from 4.7 to 10.7 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…adjacent soils and waters (Peng et al, 2017;Zhang et al, 2021), we detected these genes in all 48 manures in this The concentrations measured in our study were consistent with those detected in manure holding pits measured in other studies (Mackie et al, 2006;Joy et al, 2013;Hall et al, 2020;Alt et al, 2021) and also demonstrate the wide variations of ARGs that can be observed within manures, with variations up to three-fold. The wide ranges of measured ermB and tetM in these manures may be caused by covariates in manure holding pits that have yet unknown implications on ARG concentrations after long-term exposure such as concentrations of heavy metals, manure pit additives, or changes in chemical properties such as pH or organic substrates (Hölzel et al, 2012;He et al, 2020).…”
Section: Concentrations Of Ermb and Tetm In Swine Manure Pits (Conven...supporting
confidence: 92%
See 1 more Smart Citation
“…adjacent soils and waters (Peng et al, 2017;Zhang et al, 2021), we detected these genes in all 48 manures in this The concentrations measured in our study were consistent with those detected in manure holding pits measured in other studies (Mackie et al, 2006;Joy et al, 2013;Hall et al, 2020;Alt et al, 2021) and also demonstrate the wide variations of ARGs that can be observed within manures, with variations up to three-fold. The wide ranges of measured ermB and tetM in these manures may be caused by covariates in manure holding pits that have yet unknown implications on ARG concentrations after long-term exposure such as concentrations of heavy metals, manure pit additives, or changes in chemical properties such as pH or organic substrates (Hölzel et al, 2012;He et al, 2020).…”
Section: Concentrations Of Ermb and Tetm In Swine Manure Pits (Conven...supporting
confidence: 92%
“…In this study, we expand our knowledge of the presence of antibiotic resistant determinants in swine manure by providing a broad comparison of ARGs among manures from 48 farms. We aimed to quantify the presence of ARGs that have been demonstrated to be consistently enriched in swine manures, tetM and ermB (Whitehead and Cotta, 2013;Wen et al, 2019;Alt et al, 2021) and also characterized the presence of diverse resistance genes associated with other antibiotics and with swine manure, including aminoglycoside, carbapenem, lincosamide, phenicol, and sulfonamide resistance (Table 1). Our justification for the gene selection is that these genes are associated with the most sold antibiotics in swine production (Center for Veterinary Medicine, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The tetM gene has the widest bacteria host range of all tetracycline genes and is considered highly transferable, being located on transposons and integrases (Roberts, 2005). A previous study reported tetM gene copies as three times more abundant than 16S genes in a swine manure storage pit in Iowa (Alt et al, 2021). Notably, TET genes were present in all manure samples, with the highest number of different genes detections in samples 12 and 13 (Figure 3).…”
Section: Antimicrobial Resistance Gene Detectionsmentioning
confidence: 91%
“…Antibiotic pollution of farmland soil has become a key factor influencing the sustainability of agricultural ecosystems [ 1 , 2 ]. The application of animal manure and manure-based fertilizers is the main way for antibiotics to enter the farmland soil, due to the high residual concentrations of antibiotics in animal feces or urine in intensive farming systems [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%